Disseminated Staphylococcal Disease Complicated with Intracranial Internal Carotid Artery Mycotic Pseudoaneurysm and Cerebral Infarcts—A Rare Presentation in a Malnourished Child - Das, Suman; Ray, Biman Kanti; Chakraborty, Uddalak; Kabiraj, Sujoy (Journal of Pediatric Neurology, 2022)
A 2.5-year-old girl child patient with moderate malnutrition presented with right forehead abscess followed by ipsilateral orbital cellulitis. She also developed a left hydropneumothorax within a week. Subsequently she had left focal onset seizures with secondary generalized status epilepticus followed by development of left hemiparesis. Neuroimaging showed infarcts of varying ages in the right cerebral hemisphere and basal ganglia. Angiography revealed right internal carotid artery pseudoaneurysm. Blood and pus cultures grew methicillin-resistant Staphylococcus aureus (MRSA). Investigations for immunodeficiency were negative. The patient received vancomycin intravenously for 6 weeks and intercostal tube drainage for hydropneumothorax. She was discharged with an antiepileptic drug and aspirin. There was complete resolution of the orbital cellulitis and hydropneumothorax and also the pseudoaneurysm on follow-up angiography 3 months later.
Keywords: Staphylococcus; orbital cellulitis; Pseudoaneurysm; infarcts; vancomycin